Kinetic Modeling for Environmental Systems - Abdel Rahman, Rehab O. (IntechOpen, 2019)
The continuous increase in human activities affects the environment in notable ways; these effects need to be monitored and controlled when appropriate to ensure the sustainability of our lives. Environmental pollution is one of the major problems associated with human activities as a result of routine and accidental releases. Currently, pollution prevention, control, and affected environment remediation receive great attention globally. This attention has led to a continuous increase in research efforts that aim to understand, simulate, and predict important processes that affect pollutant generation and migration. Optimization of chemical and physical reactions within different waste treatment technologies and remediation projects are the focus of many research projects worldwide. This book presents some kinetic models that could be used to support pollution prevention, control, and environmental assessments of human activities.